BULANGO ULU RESERVOIR OPERATIONAL PATTERN MODEL - Nani, Elma; Labdul, Barry Yusuf; Husnan, Rawiyah; Nani, Elma Tiani (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2024)
The Bulango Ulu Reservoir is located in Gorontalo Province, the construction of the Bulango Ulu Reservoir is to meet the needs of raw water, irrigation water, and hydropower, to ensure whether the need and availability of water in the rainy and dry seasons can meet the initial planning goals. In this study, the method used is to simulate the operation pattern of the reservoir with variations in the wet season with the probability of discharge (66.67%), the normal season with the probability of discharge (50%), and the dry season with the probability of discharge (33.33%) so as to determine the availability of the Bulango Ulu Reservoir during the rainy season and dry season whether the needs can be met. The results obtained can be used as input for the regulation of the Bulango Ulu Reservoir operation pattern.